Covalent coupling of gum arabic onto superparamagnetic iron oxide nanoparticles for MRI cell labeling: physicochemical and in vitro characterization. (12th March 2015) - Palma, Susana I. C. J.; Carvalho, Alexandra; Silva, Joana; Martins, Pedro; Marciello, Marzia; Fernandes, Alexandra R.; del Puerto Morales, Maria; Roque, Ana C. A.
<x xml:space="preserve">Abstract</x> Gum arabic (GA) is a hydrophilic composite polysaccharide derived from exudates of Acacia senegal and Acacia seyal trees. It is biocompatible, possesses emulsifying and stabilizing properties and has been explored as coating agent of nanomaterials for biomedical applications, namely magnetic nanoparticles (MNPs). Previous studies focused on the adsorption of GA onto MNPs produced by co‐precipitation methods. In this work, MNPs produced by a thermal decomposition method, known to produce uniform particles with better crystalline properties, were used for the covalent coupling of GA through its free amine groups, which increases the stability of the coating layer. The MNPs were produced by thermal decomposition of Fe(acac)3 in organic solvent and, after ligand‐exchange with meso‐2, 3‐dimercaptosuccinic acid (DMSA), GA coating was achieved by the establishment of a covalent bond between DMSA and GA moieties. Clusters of several magnetic cores entrapped in a shell of GA were obtained, with good colloidal stability and promising magnetic relaxation properties (r2/r1 ratio of 350). HCT116 colorectal carcinoma cell line was used for in vitro cytotoxicity evaluation and cell‐labeling efficiency studies. We show that, upon administration at the respective IC50, GA coating enhances MNP cellular uptake by 19 times compared to particles bearing only DMSA moieties. Accordingly, in vitro MR images of cells incubated with increasing concentrations of GA‐coated MNP present dose‐dependent contrast enhancement. The obtained results suggest that the GA magnetic nanosystem could be used as a MRI contrast agent for cell‐labeling applications. Copyright © 2015 John Wiley & Sons, Ltd.